ANALISIS EFEKTIVITAS PENGGUNAAN MEDIA POWER POINT DALAM PEMBELAJARAN FIQIH KELAS XII DI SMA MUHAMMADIYAH PROGRAM KHUSUS SAMBI TAHUN AJARAN 2023/2024 - Majid, Aulia; Hidayah, Nur; Rochmawan, Alfian Eko (MAMBA'UL 'ULUM, 2024)
The purpose of this study is to determine how the effectiveness of the use of power point media in learning fiqh class XII and to find out what are the supporting and inhibiting factors in the use of power point media in learning fiqh class XII at SMA Muhammadiyah Special Program Sambi in the 2023/2024 Academic Yaer. The type of research in writing this thesis is qualitative research. Where this research aims to nderstand the phenomena experienced by the subject holistically and descriptively in using different natural phenomena. Data processing techniques and data analysis used through three stages, namely data reduction, presentation of information and conclusion drawing. The result showed that the use of power point media in learning fiqh class XII at SMA Muhammadiyah Special Program Sambi is effective with the increase in learning facilities/resouurces in fiqh learning subjects, learning methods used by fiqh teachers do not make students passive. Supporting factors in the use of power point media include the support of the principal and a conducive learning environment while the inhibiting factor in the lack of availability of lcd projectors so that it can hinder learning activities and lack of creativity of education in presenting so that students are monotonous to the teacher’s delivery.